Runoff and soil loss estimation using hydrological models, remote sensing and GIS in Shivalik foothills: a review - YOUSU, ABRAR; SINGH, M. J. (Journal of Soil and Water Conservation, 2020)
Shivalik foothills are considered as one of the eight most degraded eco-systems of the country. A large portion of monsoon rainfall goes as runoff in the torrents originating from the Shivalik foothills. The average annual soil loss in the Shivalik foothills is 16 t ha-1 year-1 and in some watersheds it is more than 80 t ha-1 year-1 owing to steep slopes, lack of vegetation and high intensity rainfall storms. Hydrological models, remote sensing and GIS techniques can be applied to quantify runoff and soil loss from the watersheds because manual quantification of runoff and soil loss is difficult, laborious and cumbersome. Different hydrological models are available and have been used individually and in conjunction with remote sensing and GIS to simulate and quantify runoff and soil loss from the watersheds in Shivalik foothills. Empirical and semi-empirical models like SCS curve number method, USLE, MUSLE, RUSLE and Morgan–Morgan–Finney model when integrated with remote sensing and GIS have proved to be more efficient in predicting runoff and soil loss both at field as well as at watershed scale. Deterministic models like ROMO2D, DREAM and WEPP models tested in different regions of lower Shivaliks also gave satisfactory results although their input data requirement is high. So empirical and semi-empirical models integrated with remote sensing and GIS as well as deterministic models can be successfully used for development of decision support systems for soil and water conservation planning in the region.